Effects of Green Tea Extract (Camellia sinensis L.) on Blood Biochemical Parameters in Paracetamol-Induced Wistar Rats - Galih, Damar; Indriyani, Indriyani; Septiningtyas, Sinta Dwi; Christijanti, Wulan; Susanti, R.; Marianti, Aditya (Jurnal Kebidanan dan Kesehatan Tradisional, 2026)
Background: Paracetamol is one of the analgesics and antipyretics that are widely traded freely, so it is possible that the use is not according to the recommended dose and consumption time. This can trigger liver damage and changes in blood biochemistry. Green tea has components such as antioxidants, anti-inflammatories, and hepatoprotectors. The study aimed to analyze the effect of green tea extract on the blood biochemistry of rats induced by paracetamol. Methods: Laboratory experimental research with the Post-Test Control Group Design method, using 25 male Wistar rats, applying random sampling. Twenty-five rats were divided into 5 groups: K- (control), K+ (positive control), and treatment groups with green tea extract, respectively 175 mg (T1), 350 mg (T2), and 700 mg/kg bw (T3) for 24 days. The treatment group and K+ received paracetamol 600 mg/kg bw on the 14th day for 10 days, and green tea extract was still given. Data, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), triglycerides (TG), total cholesterol, and leukocyte counts, were analysed using ANOVA and the Least Significant Difference (LSD) test. Results: GTE significantly (p-value <0.05) reduced leukocytes and AST, but inadequate paracetamol induction failed to elevate ALT and lipids, masking GTE’s measurable impact on those specific biochemical parameters. Conclusion: Providing green tea extract was effective in declining the number of leucocytes and AST levels. The study concluded that green tea extract has the potential to influence the biochemical profile of rats induced by paracetamol. Further research is needed regarding the dose and period of administration and exposure.